Examining the Determinants of Managers' Hiring Attitudes Towards Immigrant Workers: Evidence from an Employer Survey - Tony Fang; Tingting Zhang; John Hartley (Institute of Labor Economics (IZA), 2023)
Using a representative survey of 801 employers across Atlantic Canada, we empirically test various factors associated with employer hiring attitudes towards international migrants. Our results indicate that employers who hired international immigrants in the past 12 months exhibited more positive attitudes towards them, consistent with the contact theory. We also find provincial variations in hiring attitudes in that employers in Nova Scotia, Newfoundland, and PEI had more positive attitudes than those in New Brunswick. In addition, employers in the public sector organizations held more positive perceptions than those in the private sector. Although the coefficients for rural-urban divide and organizational sizes have the expected signs but most of them are statistically insignificant. There are no clear patterns cross industries. Interpretations for our main findings are offered, along with policy and practice implications
Keywords: J23; J61; J63; J68; 330; international immigrants; labour and skill shortages; employer hiring attitudes; employer survey; Atlantic Canada